2013
DOI: 10.1785/0120120214
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a New Velocity Structure Inversion Method Based on Horizontal-to-Vertical (H/V) Spectral Ratios of Earthquake Motions in the Tohoku Area, Japan

Abstract: International audienceThe earthquake motion generated by the multiple scattering due to the complexity of the underneath soil structure can be referred to as a diffuse wave field. Under the assumption of the well-diffused wave field it is accepted that the average autocorrelation of a single receiver is proportional to the imaginary part of the Green's function when both source and receiver are located at the same point. In this study we focus on sites where the site effect can be described using a 1D model. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The square root of the bedrock's P-and S-wave velocity ratio is used as a correction coefficient for the incident wave amplitude. The validity of the method used to derive underground S-wave structures from EHVRs has been reported by Ducellier et al (2013) and Nagashima et al (2014). On the other hand, Salinas et al (2014) compared observed EHVR and MHVR at one site inside the Mexico City basin and found that the observed EHVR is similar to the theoretical MHVR, especially in the high-frequency range.…”
Section: Introductionmentioning
confidence: 70%
“…The square root of the bedrock's P-and S-wave velocity ratio is used as a correction coefficient for the incident wave amplitude. The validity of the method used to derive underground S-wave structures from EHVRs has been reported by Ducellier et al (2013) and Nagashima et al (2014). On the other hand, Salinas et al (2014) compared observed EHVR and MHVR at one site inside the Mexico City basin and found that the observed EHVR is similar to the theoretical MHVR, especially in the high-frequency range.…”
Section: Introductionmentioning
confidence: 70%
“…Then, Kawase et al (2011) extended the idea of DFC to the stack of horizontal-to-vertical ratios of earthquakes (EHVR) and provided a simple theoretical formula assuming equipartition of energy in the incident waves at the bedrock (i.e., equipartition inside the half-space). It turned out that this is a powerful tool to determine the S-wave velocity structure below the observed site of earthquakes down to the seismological bedrock, as evidenced by Ducellier et al (2013), Nagashima et al (2014Nagashima et al ( , 2017 and Fukihara et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the resolution of 1-D seismic profiles depends on the distance between acquisitions points with borehole measurements that can be averaged to get smooth variations (Moss 2008). Arai & Tokimatsu (2005) and Ducellier et al (2011) among others performed a sensitivity analysis to determine which soil parameters controlled, in the inversion process, the H/V (horizontal to vertical) curves obtained from seismic ambient noise measurements, defined on a specific frequency range. Moreover, the resolution provided by each method must be kept in mind while building a numerical model based on real data.…”
mentioning
confidence: 99%